Africa agriculture status report 2014: Climate change and smallholder agriculture in sub-saharan Africa - Alliance for a Green Revolution in Africa (Alliance for a Green Revolution in Africa, 2014)
As the second in the series of the African Agriculture Status Report, this volume seeks to provide an in-depth and comprehensive analysis of emerging issues and challenges faced by African smallholder farmers, and allow scholars and professionals to contribute practical and evidence-based solutions. The Report documents the effects of climate change on smallholders in Africa, the ongoing adaptation by farmers and livestock keepers, constraints to adoption of climate-smart technologies, and highlights areas where investments in African agriculture have the potential to be most productive. It seeks to help African agricultural policy makers and stakeholders identify climate change issues and challenges, as well as appropriate climate-smart agriculture practices and policies that can help smallholder farmers sustain and improve their livelihoods – that can increase productivity and incomes, enhance adaptation and build resilience to climate change, and reduce GHG emissions by Africa’s agricultural producers and processors.